The caregivers' dilemma: Care burden, rejection, and caregiving behaviors among the caregivers of patients with depressive disorders. (May 2020) - Yu, Sheng-Hsiang; Wang, Lun-Ting; SzuTu, Whey-Jan; Huang, Li-Chung; Shen, Cheng-Che; Chen, Ching-Yen
Highlights: The higher care burden caregivers experienced, the more severe depression they had. Caregivers' own depression predicted rejection, rather than caregiving behaviors. Subjective burden can predicted both caregivers' rejection and caregiving behaviors. Objective care burden was not significantly associated with rejection and caregiving behaviors. Reassurance seeking predicted increased, rather than reduced, caregiving behaviors. Abstract: Taking care of depressed patients significantly impacts caregivers' lives, both objectively and subjectively. The effects of caregivers' burden on their responses to their patients has yet to be investigated. The aim of this study is to explore the relationships among caregivers' subjective and objective burden, depression, frequency of caregiving behaviors, and rejective attitude. A cross-sectional study was conducted among 134 caregivers of patients diagnosed with depressive disorders. We administered questionnaire to assess caregivers' demographics, care burden, reassurance seeking, depression, rejective attitude and caring behaviors. Both caregivers' objective and subjective burdens were associated with their depressive symptoms. Rejection towards patients was determined by the caregivers' level of depressive symptoms, subjective feeling of sadness, and anger, rather than by their objective burden. On the other hand, the frequency of caregiving behavior was determined by perceived reassurance seeking and anger, rather than by caregivers' depression or objective burden. These findings suggest that caregivers' subjective burden plays a more salient role in predicting their rejection and frequency of caregiving behaviors toward the patients than objective burden. The caregivers in this study could recognize their rejective attitude toward depressed patients but still had difficulty withdrawing their care when they were already in distress.